Should We Perform Repeated Re-biopsy for the Detection of T790M Mutation? - Kim, Saerom; Kim, Soo Han; Kim, Jinmi; Kim, Mi-Hyun; Lee, Min Ki; Eom, Jung Seop (Cancer research and treatment, 2023)
Purpose Epidermal growth factor receptor (EGFR) T790M mutations have been detected in the second or third rebiopsy, even if the T790M mutation was not identified in the first rebiopsy. This meta-analysis investigated the EGFR T790M mutation detection rates and its additional advantages with repeated rebiopsies.Materials and Methods We searched through the PubMed and EMBASE databases up to June 2022. Studies reporting rebiopsy to identify the EGFR T790M mutation in case of disease progression among patients with advanced non-small cell lung cancer and multiple rebiopsies were included. The quality of the included studies was checked using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool.Results Eight studies meeting the eligibility criteria, reporting 1,031 EGFR mutation–positive patients were selected. The pooled EGFR T790M mutation detection rate of the first and repeated rebiopsies were 0.442 (95% confidence interval [CI], 0.411 to 0.473; I2=84%; p < 0.01) and 0.465 (95% CI, 0.400 to 0.530; I2=69%; p < 0.01), respectively. Overall, the pooled detection rate of EGFR T790M mutation was 0.545 (95% CI, 0.513 to 0.576), which increased by 10.3% with repeated rebiopsies.Conclusion This meta-analysis identified that repeated rebiopsy increases the detection rate of EGFR T790M mutation by 10.3%, even if EGFR T790M mutation is not detected in the first rebiopsy. Our results indicate that the spatiotemporal T790M heterogeneity can be overcome with repeated rebiopsy.